Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

Business combinations and group of companies : perspectives from accounting, law and corporate finance - Coda, Stefano (Université Paris 1, 2018)
Dans le cadre général des regroupements d'entreprises et des groupes de sociétés, cette thèse porte sur des questions d'intérêt à la croisée de la comptabilité, du droit (notamment les dispositions légales et la réglementation comptable) et de la finance d'entreprise. En ce qui concerne la théorie comptable, le chapitre 2 étudie comment les chercheurs en économie d'entreprise ont compris les groupes d'entreprises, les comptes de groupe et le processus de leur préparation, en particulier par rapport aux juristes italiens. Ensuite, le chapitre 3 reconstruit le processus politique et législatif qui a engendré la naissance du concept de groupe de sociétés dans le corpus juridique italien.Concernant le droit et la politique comptable, une analyse comparative est effectuée au chapitre 4qui montre clairement l'évolution de la notion de contrôle et de son utilisation dans les comptes consolidés (comptes de groupe) et les regroupements d'entreprises (I) en droit européen, (II) selon les normes comptables internationales publiées par l'IASB (International Accounting Standards Board) et (III) par rapport aux principes comptables généralement admis aux États-Unis («USGAAP»). De plus, les chapitres 5 et 6 étudient les effets du lobbying sur les normes comptables concernant les états financiers consolidés et les regroupements d'entreprises publiés par l'IASB. Fait intéressant, les résultats concordent avec une forme de capture du normalisateur comptable international par une catégorie d'institutions financières. En effet, confrontées à un modèle de consolidation prétendument basé sur le contrôle, ces dernières ont plaidé en faveur d'une exception de consolidation fondée sur un modèle de propriété et documentée comme ayant été proposée par les sociétés d'audit américaines dans ce contexte au moins depuis 1995. Ce modèle s’avère avoir trouvé un terrain fertile au sein de l'IASB. En conséquence, d'autres catégories d'institutions financières,telles que les fonds d'investissement à long terme et ceux gérés par une famille tout en préférant un modèle de consolidation différent, ne sont plus autorisées à présenter des états financiers consolidés. En ce qui concerne la finance d’entreprise, le chapitre 7 analyse les implications de différentes décisions de financement dans un nouveau échantillon de fusions et acquisitions entre institutions financières (banques et assurances) consommées dans le monde entier au cours des deux dernières décennies. En particulier, il étudie (I) la relation entre la méthode de choix de paiement (si le prix est payé en cash, en actions ou une combinaison des deux) et le choix du mode de financement d'un regroupement d'entreprises (y compris les instruments hybrides) et (II) la réaction des investisseurs à l'annonce de la combinaison. En ce qui concerne ce dernier point, l'utilisation de deux tests non paramétriques permet de détecter une relation intéressante entre la réaction du marché à l'annonce et les différents modes attendus de financement de la transaction.
Keywords: Accountings standard setting; Comptabilité; Consolidation exemption; Egroupements d'entreprises; Finance d'entreprise; Finances; Financial institutions; Gestion d'entreprise; Groupes de sociétés; IASB; IFRS 10; IFRS 3; Mergers and acquisitions; Method of payment; Politics; Politique comptable; Sources of fundings; Économie d'entreprise

Relations between quality of trademarks and cognitive and conative variables of consumers - Naumovski, Goce (Université de Strasbourg, 2018)
But de la recherche : déterminer la dépendance des caractéristiques des marques (perceptibilité visuelle, représentation graphique, le caractère distinctif, non-généricité etc.), sur les types généraux spécifiques de capacités intellectuelles et sur les caractéristiques conatives des consommateurs de la population générale, par application de nombreux tests. La recherche a été réalisée sur un échantillon de 206 sujets-consommateurs. Ils ont évalué la qualité des marques de commerce (déposées et refusées) pour différents types de produits et services (TM-1 test). Les sujets ont été testés avec 3 tests cognitifs et 6 tests conatifs. Méthodes quantitatives appliquées : paramètres élémentaires de la statistique descriptive ; corrélation ; analyse factorielle ; analyse de régression multivariée, analyse canonique des corrélations. Les résultats ont indiqué que les variables cognitives et conatives ont des relations statistiquement significatives avec les résultats de TM test (qualité des marques).
Keywords: Capacités cognitives; Caractéristiques conatives; Cognitive abilties; Comportement des consommateurs; Conative characteristics; Consommateur; Consumers; Intellectual property; Marques; Marques de commerce (droit international); Propriété intellectuelle (droit international); Trademarks

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

Combating corruption in public procurement in developing countries : a legal analysis - Mugadza, W. T. (North-West University, 2018)
This study was motivated by the quest to find new innovative and practical ways of combating public procurement corruption in developing countries to complement the existing measures. This was achieved by comparing three jurisdictions, Hong Kong-China, Botswana and South Africa. The focus was on how each jurisdiction uses the following four measures to curb public procurement corruption: criminal measures; administrative measures; institutional measures and civil activism measures. It was established that Hong Kong uses what this study has classified as the traditional approach of combating public procurement corruption. The traditional approach is characterised by the use of a separate procurement legal framework and a separate corruption legal framework to curb public procurement corruption. Its strengths are in the strict enforcement of criminal measures that are anchored on a robust legal framework, a clear anti-corruption strategy, an independent anti-corruption agency (institutional measure), effective internal oversight and a strong political will. However, the following weaknesses of the traditional approach were identified: over reliance on criminal measures; excessive dependence on one enforcement institution; it neglects the development of administrative measures and has weak civil activism measures. It was established that Botswana uses what this study has classified as the classical approach of combating public procurement corruption. The classical approach is characterised by a procurement legal framework that incorporates very minimum anti-corruption provisions. The anti-corruption provisions in the procurement legislation are enforced by an external institution (the DCEC in the case of Botswana) which relies heavily on the criminal measures. Its strengths are the following: a strong legal framework which provides for a clear anti-corruption strategy; it has anti-corruption units in each Ministry and it has a dedicated Corruption Court. However, the classical approach has the following weaknesses: the anti-corruption agency is not adequately independent as it under the control of the executive (the President in the case of Botswana); lacks effective internal oversight mechanisms; weak political will; neglects the development of administrative measures and civil activism measures are almost non-existent save for the media. It was established that South Africa uses what this study has classified as the traditional cum silo approach of combating public procurement corruption. The traditional cum approach is characterised by multiple procurement legislation which has certain but minimum anti-corruption provisions and a separate corruption legal framework. Multiple anti-corruption agencies are prone to political interference which renders them ineffective and unfit for purpose. Its strength is in the promotion and protection of civil activism measures (right to access information, right to freedom of speech and legal protection of whistle-blowers). Notable weaknesses of the traditional cum silo approach are: the poor enforcement of criminal measures; there is no lead anti-corruption agency that spearheads and coordinates all cases of public procurement corruption; there is no clear anti-corruption strategy; the administrative measures such as debarment are poorly enforced; it has multiple anti-corruption institutions that lack focus and professionalism which results in political manipulation. The thesis concluded by suggesting a new approach, the contemporary approach to combating public procurement corruption which entails the enactment of a single procurement legislation (model law) the Public Procurement and Combating of Public Procurement Corruption Act (hereafter PPCPPC). The contemporary approach advocates for the regulation of public procurement and the combating of public procurement corruption in one legislation. This legislation (PPCPPC) takes into account, the current demands for public procurement as well as future developments of public procurement. These include but are not limited to self-cleaning, cyber-crime and public procurement corruption as well as the role of foreign convictions for debarment purposes. The envisaged PPCPPC will in addition to regulating public procurement, encompass the best criminal measures, administrative measures, institutional measures and civil activism measures. In addition, the contemporary approach through the PPCPPC proposes two new innovations: the corruption clearance certificate and a mandatory anti-corruption clause in all government contracts.
Keywords: Accountability; Administrative measures; Anti-corruption clause; Botswana; Civil activism measures; Classical approach; Combating corruption; Competitiveness; Contemporary approach; Corruption clearance; Criminal measures; Debarment; Equality; Fairness; Hong Kong; Institutional measures; Integrity; Procurement principles; Public procurement; South Africa; Traditional approach; Transparency; Value for money

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Internet regulation and development: the battle over the network neutrality - Melo, Lílian Manoela Monteiro Cintra de (Universidade de São Paulo, 2018)
We have arrived at crossroads in the debates about the future of the internet governance. It is high time to address the reasons why policy choices have not been sufficient to preserve the internet\'s promise to bring about development, democratic engagement, and social justice. The network neutrality is central to this debate since it intersects all internet layers and is related to most contemporary issues that will shape future of the internet. My assumption is that network neutrality\'s failures are not an unintended consequence of the regulatory system, but part of the problem. My core hypothesis is that network neutrality\'s limits mainly occur because of, first, its inability to secure all envisioned goals and, second, its decontextualized focus on innovation on the last mile of the internet distributional chain. The network neutrality debate has produced a wide variety of work embedded within economic and legal studies regarding what would be necessary to guarantee a free and innovative internet. Although this work has been often disguised under the mask of technique, it is widespread influenced by the evolutionary economics and denies the network neutrality's effects on ongoing struggles for social and economic justice. My proposition is that network neutrality debate has failed because it proved unable to address the problems related to concentrated power structures on the internet and increasing inequalities. To achieve this objective, this dissertation investigates the network neutrality debate over the last decades to identify processes and mechanisms by which its sterile arrangements came to take specific form in time and place, focusing on what such arrangements might inform about contemporary policy efforts. In Chapter 1, prevalent internet governance myths are deconstructed, presenting how specific architecture design and the corresponding network neutrality outcomes came to prevail in particular periods. Drawing upon and integration of distinct source materials, Chapters 2 and 3 identify the specific contingencies over the past decades by which a dynamic set of evolving actors, events, and institutions converged (or not) and gave rise to current network neutrality rules and dissent in the United States and Brazil. At the center of the analysis is the identification of structures and power struggles. Finally, Chapter 4 aims at presenting a new framework towards the network neutrality debate and its potential distributive effects in the global economy, taking technology not as deterministic but embedded and being embedded in all the building blocks of what we term the social.
Keywords: Economic power; ICT; Inequality; Innovation; Internet access; Internet governance; Law and development; Network neutrality; S&TS; Structure

Contract, Conflict and Cooperation: A Critical Analysis of the Common Law Approach to the Breakdown of Modern, Complex, Symbiotic Contracts - Soper, Charles Haward (University of Leicester, 2018)
The springboard of a real-world, doctrinal, and theoretical investigation of the role played by cooperation in complex modern contracts allows me to articulate and justify a deep and concrete Transcendent Duty to Cooperate (TDTC) for these contracts. The source of the TDTC is the express words and/or the background of such contracts, the commercial expectations of the parties; which reveal that successful performance re-quires cooperation. The inevitable inference from this is that parties implicitly agree to cooperate. As the duty is implicit, it follows, I argue, that there are no gaps to be filled; merely meaning to be unearthed from the words and/or the background (construction). In doctrinal work, I review cases in categories (prevention, facilitation, defect-rectification, communication, decision-making, and active cooperation), showing that the law is far from coherent but also far from incoherent. Shifting from judicial policy making and gap-filling to context/purpose based contract construction, using evidence, is possible and would provide coherence. I create a clear and enforceable definition of cooperation through analysing the opinions of around five-hundred commercial experts and synthesising those with doctrine and theory. My empirical work analyses experts’ views; collected by interview, an online survey and workshops, using vignettes developed from adjudicated/real-life cases including opinion on what cooperation is and how it is achieved. The findings of my survey are compared with others. At an abstract level, it aligns with comparable surveys and at a detailed level, it is unique. In theoretical work, I show that basing the TDTC on construction is superior and more efficient, brings coherence to the law and that it is underpinned by shared, normative, “community” values. I test the TDTC against various “hard” cases, analysing remedial issues, showing that it would not decrease certainty in English Commercial Law, and is defensible by an appeal for coherence.

Enabling intellectual property and innovation systems for South Africa's development and competitiveness - Sibanda, McLean (University of South Africa, 2018)
During the last two decades, there have been a number of policy and legislative changes in respect of South Africa’s intellectual property (IP) and the national system of innovation (NSI). In 2012, a Ministerial Review of the Science, Technology and Innovation (STI) landscape in South Africa made recommendations to improve the STI landscape and effectively the national system of innovation. The study provides a critical review of drafts of the national IP policy published in 2013 as well as the IP Framework released in 2016 for public comment. The review of the IP and the NSI are within the context of the National Development Plan (NDP), which outlines South Africa’s desired developmental goals. South Africa is part of the BRICS group of countries (Brazil, Russia, India, China and South Africa). The South African economy is characterised by a desire to move away from being dependent on resources and commodities, to becoming a more knowledge based and innovation driven economy. It is hoped that such a move would assist the country to address some of the social and economic development challenges facing South Africa, as captured in the NDP. South Africa has a functioning IP system, but its relationship with South Africa’s development trajectory is not established. More particularly, the extent to which the IP system relates to the innovation system and how these two systems must be aligned to enable South Africa to transition successfully from a country based on the production of primary resources and associated commodity-based industries to a viable knowledge-based economy is unclear. The Trade-related Aspects of Intellectual Property Rights (TRIPS Agreement) of the World Trade Organisation (WTO) provides that IP must contribute to innovation and to transfer of technology and knowledge in a manner that is conducive to social and economic welfare. Certain provisions set out the foundations of intellectual property systems within the context of each member state. This study has thus explored the complex, complementary and sometimes contested relationships between IP and innovation, with particular emphasis on the potential of an intellectual property system to stimulate innovation and foster social and economic development. The study has also analysed the interconnectivity of IP and innovation with other WTO legal instruments, taking into account South Africa’s positioning within the globalised economy and in particular the BRICS group of countries. The research involved a critical review of South Africa’s IP and innovation policies, as well as relevant legislation, instruments, infrastructure, IP and innovation landscape, and relationship with international WTO legal instruments, in addition to its performance, given the developmental priorities and the globalised economy. The research documents patenting trends by South Africans using European Patent Office (EPO), Patent Cooperation Treaty (PCT), United States Patents and Trademarks Office (USPTO) databases over the period 1996-2015. A comparative analysis of patenting trends amongst BRICS group of countries has also been documented. The study also documents new findings, observations and insights regarding South Africa’s IP and innovation systems. Some of these, particularly in relation to higher education and research institutions, are directly attributable to the Intellectual Property Rights from Publicly Financed Research and Development Act. More particularly, the public institutions are becoming relevant players in the NSI and are responsible for growth of certain technology clusters, in particular, biotechnology. At the same time, the study makes findings of a decline of private sector participation in patenting as well as R&D investment over the 20-year period. Recommendations are included regarding specific interventions to ensure coherence between the IP and innovation systems. Such coherence and alignment should strengthen the systems’ ability to stimulate innovation and foster inclusive development and competitiveness, which are relevant for addressing South Africa’s socio-economic development priorities.
Keywords: BRICS; Biopharmaceutical; Biotechnology; Commercialisation; Economic development; Flexibilities; Inclusive growth; Innovation; Intellectual property; Licensing; Patents; Start-ups; TRIPs Agreement

A critical analysis of the removal of directors by the board of directors and the judiciary under the Companies Act 71 of 2008 - Cassim, Rehana (University of South Africa, 2018)
Section 71(3) of the Companies Act 71 of 2008 has introduced into South African company law a provision which for the first time permits the board of directors to remove another director from office in certain specific instances. A further significant innovation in the Companies Act 71 of 2008 is contained in section 162, which empowers a court to make an order declaring a director delinquent or placing him under probation in specific instances. The effect of section 162 is that a court is empowered to remove a director from the board of directors. The focus of this thesis is the removal of directors from office by the board of directors and by the judiciary. The thesis explores the underpinning philosophy of the statutory provisions relating to the removal of directors from office. It also examines the impact of the power given to the board of directors and to the courts to remove a director from office. The grounds and the procedures for the removal of directors by the board of directors and the judiciary are examined. The fiduciary duties applicable to directors in removing a director from the board of directors are also explored. In addition, this thesis examines the removal of directors holding multiple positions or capacities in relation to a company, such as an employee or a shareholder with loaded voting rights. The remedies which may be relied on by a director who has been removed from office by the board of directors are examined. Recommendations are made to strengthen and improve the provisions in the Companies Act 71 of 2008 relating to the removal of directors from office by the board of directors and the judiciary. Amendments to the Companies Act 71 of 2008 are suggested to remove ambiguities; to guard against the abuse of sections 71(3) and 162; to improve the grounds and procedures for the removal of directors by the board of directors and the judiciary, and to enhance the remedies that may be relied on by a director who has been removed from office by the board of directors.
Keywords: Corporate governance; Directors and shareholders power; Directors of corporations; Fiduciary duties; Investor relations; Removal of directors from office; Stockholders' voting; Voting rights

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
URI: http://hdl.handle.net/10019.1/103466
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
URI: http://hdl.handle.net/10019.1/103776
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

The Impact of Private Securities Lawsuits on Accounting Conservatism and the Moderating Influence of Corporate Governance - Kerr, Ryan (Victoria University of Wellington, 2018)
This study investigates the impact of conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit, on the level of accounting conservatism in financial reporting. This study also investigates the moderating influence of corporate governance on the level of accounting conservatism following conduct which goes on to give rise to a securities lawsuit, and the filing of a securities lawsuit. The study uses a sample of 617 privately enforced disclosure-related securities lawsuits against listed US firms, taken under SEC rule 10b-5 of the 1934 Securities Exchange Act, over the period 2002 to 2010. The results of the study indicate that following both the conduct that gives rise to a securities lawsuit, and the filing of a securities lawsuit, firms adopt higher levels of accounting conservatism. However, the study finds no evidence that corporate governance moderates the impact of securities lawsuits on the level of accounting conservatism.
Keywords: Accounting Conservatism; Governance; Securities Lawsuits

An evaluation of market responses to corporate disclosures in a continuous disclosure environment - Li, Hanqiao (Victoria University of Wellington, 2018)
Corporate disclosure has attracted the attention of researchers from the accounting and capital markets. Researchers have been trying to better understand how capital markets respond to corporate disclosures. This study explores the short- and the long- term market effects of corporate disclosures in a continuous disclosure environment. This study aims to find the answers to the following research questions. (1) How market (price/volume) sensitive is the information contained in each disclosure category in a continuous disclosure environment? (2) How quickly is the value-relevant information incorporated into share prices before the annual earnings announcement is released, and how can company announcements promote this timeliness of price discovery? Specifically, this study examines the extent to which the Australian share market reacts to new public information immediately after the information is released, and the impacts of announcement frequency as to different continuous disclosure categories on the timeliness of price discovery (also known as the speed of price discovery). Prior research has mostly concentrated on a single type of information event to examine the information’s market consequences by monthly, weekly or daily data. Instead, by covering all public announcements and using tick (transaction) data to calculate intraday abnormal returns and abnormal trading volumes, this study examines which type of announcement has the largest immediate market responses, and compares the magnitude (with positive/negative signs) of market reactions to different announcement categories on the Australian Securities Exchange (ASX). This study is more attractive under the Australian Continuous Disclosure Regime (CDR) because of the classification system regarding the market-sensitive announcements. Whether or not an announcement is market-sensitive is predetermined by ASX ‘specialist staff’ before the announcement is released on the market. This study investigates how the market interprets the announcement, examining market sensitivity from both the share price and trading volume movements after the announcement is available to the market. In other words, to some extent, the ‘market sensitivity tag’ shows the announcement that the market should react to, and this study reveals the announcement that the market does react to. Focusing on market-sensitive announcements, except for the ASX Query, the significant results show a positive association between announcement categories and intraday Cumulative Abnormal Returns (CARs). Share prices react the most to Progress Reports and to Asset Acquisition & Disposal, and the least to Periodic Reports and Issued Capital. Share price reactions to Distribution Announcements and Other are in the middle. There are at least two possible reasons for the different market reaction magnitudes. One is the information materiality nature: if one type of information is more important to investors than other information, this may cause higher abnormal returns on the market. The other is the information predictability: if there has been a lot of relevant information available in previous days or months, share prices could adjust to the information more smoothly. In terms of the trading volume reactions, intraday Abnormal Trading Volumes (ATVs) are observed after the release of Progress Reports, Asset Acquisition & Disposal, Issued Capital and Periodic Reports. After separating good and bad news subsamples, the results show that Progress Reports and Asset Acquisition & Disposal tend to indicate good signs to the market and cause larger trading volumes. Periodic Reports and Issued Capital could contain either good or bad news, but the trading volumes are driven by bad news. The results also reveal that company size is an important factor. Large companies tend to have relatively small market responses after information is released, which confirms that the larger companies are more stable. This study also evaluates long-term market effects of corporate disclosures by examining the timeliness of price discovery (also known as the speed of price discovery). It is the timeliness with which the full value relevant information is priced over a year before the annual earnings announcement is released. Previous literature has revealed that earnings announcements convey information, because significant stock returns or increased trading volumes are observed around the time that earnings announcements are released. However, it has also been suggested that there are other more timely information sources available that contain essentially similar or even the same value-relevant information. By the time preliminary final reports become available to the market, any potential value-relevant information has been included in the share price. The CDR again provides an attractive environment to examine the impact of corporate disclosures on the timeliness of price discovery, because listed companies have to disclose to the market before any other media sources. This enables an exploration of the relationship between the timeliness and the frequency of continuous disclosures. If the CDR is efficient in keeping investors fully informed, there should be no stock price surprise after the earnings announcement is released. Given the importance of the Preliminary Final Reports to the timeliness metric and the fact that the immediate market reaction tests only cover announcements released during trading hours, this study investigates in depth the Preliminary Final Reports and finds some evidence that companies tend to release bad news after the market closes and/or on Fridays. In terms of the impacts of announcement frequency on the timeliness of price discovery, following the step ‘All announcements – Periodic/Non-periodic announcements – Detailed categories of Non-periodic announcements’, the findings reveal that only earnings-related and cash flow announcements (Periodic Reports, Distribution Announcements and Quarterly Cash Flow Reports) can accelerate the timeliness of price discovery. Unfortunately, the results do not confirm that more announcements on the market could promote the timeliness with which the value-relevant (i.e. earning/income) information is incorporated into share prices. In addition to announcement frequency influences, the price discovery process is faster for companies with better share performance, are larger or have greater profitability. Financial companies have a timelier price discovery process than other companies; the price discovery process of financial companies was affected more by the 2008 – 2010 Global Financial Crisis than that of other companies. This study contributes to the market reaction literature by covering all categories of company announcements and comparing immediate market consequences for each type of announcement, and builds upon the timeliness of the price discovery literature by linking the announcement frequency of each continuous disclosure category to the timeliness with which annual earnings information is incorporated into share prices.
Keywords: Announcement categories; Announcement frequency; Continuous Disclosure Regime; Immediate market reactions; Market sensitivity; Timeliness of price discovery

Location data and human mobility : an evaluation of a dissonance that frames data protection and privacy rights - Andrew, Jonathan (European University Institute, 2018)
With citizens’ movements mediated by many technologies that aid our navigation the potential for omnipresent surveillance may potentially institute fundamental changes to the human condition. Locational privacy is pivotal in developing inter-personal associations and relational ties with others and its function is therefore complex, rather than solely affording a degree of independence from the observations made by others. In this respect, a more nuanced understanding of the utility of location data is required; the current hierarchy that delineates personal data from special categories of personal data does not adequately appreciate the capacity for location data to act as a proxy for other sensitive personal data. Furthermore, the binary distinction that reflects the conceptualisation of the right to privacy as a negative right, with related concepts such as identity and personality formation viewed as positive constructs, is increasingly difficult a notion to preserve. The classification and terminology of technologies can illustrate how terms and legal metaphors are developed and applied so as to bridge gaps in applying existing context and precedent. Though the designation ‘location data’ once constituted a reasonable accommodation in nomenclature as an intelligible and easily comprehensible term, even while constituting a significant oversimplification of the data it represented, technological advances have rendered the term increasingly problematic. This study asks whether the existing legal framework at the regional level in Europe is apt to provide sufficiently cogent and coherent regulation given recent developments in technologies. The review analyses the risks associated with this predilection in data processing activities that allows for the identification of ever more intimate and nuanced details of a citizen’s life, behaviours and convictions through the analysis of their location data; in turn, it shall discern the necessity of considering the resulting impacts on citizens’ fundamental rights to privacy and personal data protection.
Accepted: 2018-02-16T08:28:25Z
Keywords: Data Protection; European Union countries; Location data; Privacy

International norm conflicts through the lens of Alexy's principles theory - Böök, Birte (European University Institute, 2018)
The likelihood of clashes between international norms has increased in correlation with the upsurge in the number of specialised regimes emerging within the international legal field. The present thesis takes a closer look at the different ways in which such norm conflicts can be addressed at the international level. In particular, it distinguishes between conflict resolution based on establishing priority by means of traditional maxims, and resolution based on the weighing of clashing norms to determine which prevails in the case at hand. To do so, the thesis takes a step back from the existing literature and examines the distinction within norms between rules and principles, relying predominantly on Robert Alexy’s theory on this subject. Taking a legal-theoretical approach to the subject of international norm conflicts, this thesis shows that Alexy’s principles theory is not only transferrable to international law in theory, but that we can, moreover, identify international norms as rules and principles respectively. Distinguishing between the different ways in which conflicts are resolved depending on whether the norms involved are rules or principles, it is shown that while both approaches are susceptible to certain conceptual uncertainties and pitfalls, this dichotomy nevertheless plays an important role in the efficiency of the international legal system, ensuring that a certain balance between stability and flexibility is maintained. Ultimately, it is demonstrated that by viewing international law, and international norm conflicts in particular, through the lens of Alexy’s principles theory, we can gain a clearer understanding of the structure and application of international norms on the one hand and, as a result, how to resolve international norm conflicts on the other. Thus, drawing a distinction between rules and principles among international legal norms can be a means by which scholars (as well as judicial bodies or even states) may analyse ambiguous judicial decisions or international legal provisions, and can thus foster greater clarity in the field of international law.
Accepted: 2018-11-28T14:26:22Z
Keywords: Dispute Resolution; International Law

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
URI: https://repository.up.ac.za/handle/2263/70102
Keywords: Contract; Locatio conductio

The fairness of forfeiture clauses in short-term insurance contracts - Huneberg, Samantha (University of Johannesburg, 2018)
Insurance fraud is a major issue in the insurance industry. Insurance companies around the world are all facing significant losses due to the prevalence of fraudulent claims. These fraudulent claims and subsequent losses suffered by insurers inevitably lead to a dilution of the insurance pool and result in other policyholders bearing the brunt of these losses. The inevitable solution for insurers is to hike the premiums for all other policyholders in order to compensate for their losses caused by fraudulent claims. Insurance fraud is an international problem and it is common for insurers in most jurisdictions to use forfeiture clauses. These clauses aim to protect the insurer by stating that if the policyholder should submit any type pf fraudulent claim, the policyholder will forfeit the entire claim. There has been much controversy around the validity and fairness of these clauses. This thesis seeks to provide an overview of the prevalence of fraudulent insurance claims in South Africa, England, Australia and New Zealand. Moreover, it will consider the fairness of forfeiture clauses in light of the fundamental movement towards policyholder protection in recent years both in South Africa and in those jurisdictions that form part of the comparative study. The thesis concludes that forfeiture clauses form an indispensable part of short-term insurance contracts and are justifiable and therefore lawful. It is, however, submitted that insurance companies have a duty to disclose the nature and extent of forfeiture clauses at the inception of the policy and again at claim stage. By using so-called staggered disclosure, insurers provide policyholders with the opportunity to consider their claim and the means with which to prove it in order to avoid instituting a fraudulent claim. The thesis recommends that these rules pertaining to staggered disclosure should form part of the 2018 Policyholder Protection Rules, together with a statutory definition of insurance fraud.
Keywords: Forfeiture; Insurance policies; South Africa

A South African perspective on the meaning of "beneficial ownership" in Article 10 of the OECD Model Tax Convention on Income and Capital in the context of conduit company treaty shopping - Jansen van Rensburg, Enelia Cornelia (University of Pretoria, 2018)
The use of conduit company treaty shopping structures is often regarded as an impermissible erosion of a country’s tax base. For a developing country, such as South Africa, the protection of its tax base is an important policy consideration. Arguably, one way of combatting conduit company treaty shopping structures is by including in a country’s double taxation agreements the beneficial ownership requirement set out in Article 10(2) of the OECD MTC. The study examines how a South African court would interpret this requirement in provisions in South African double taxation agreements in the context of conduit company treaty shopping involving conduit companies receiving dividends. The study firstly considers whether the beneficial ownership requirement can be regarded as an anti-avoidance rule aimed at combatting conduit company treaty shopping falling outside agents and nominee scenarios. It further considers whether the term “beneficial owner” should have a legal or economic meaning. It explores the meanings given to this term by scholars and foreign courts and the OECD in its Commentaries to the OECD MTC. The study also considers the application of the rules of interpretation contained in the Vienna Convention on the Law of Treaties when giving meaning to this term. Lastly, the study considers whether the term should have the meaning assigned to it under the domestic law of a treaty country, or under international tax law. As part of this enquiry, the meanings of the expression “beneficial owner” in South African case law and legislation are explored.
https://repository.up.ac.za/handle/2263/65660
Keywords: Beneficial ownership; Conduit company treaty shopping; OECD; OECD Model Tax Convention; Société écran; South Africa

Modifying contract law principles to accommodate automated transactions in South Africa - Ramokanate, L. L. (North-West University, 2018)
Modern electronic commerce is chiefly characterised by the use of unattended computers in the negotiation and conclusion of agreements. Commonly referred to as "electronic agents," these computers assist their users to negotiate better and profitable deals in virtual marketplaces. In South Africa, the legal force and effect of automated transactions, i.e. agreements concluded by electronic agents, is addressed in section 20 of the Electronic Communications and Transactions Act 25 of 2002 (hereinafter referred to as the ECT Act). According to section 20 (a) of the ECT Act, a valid and enforceable agreement will be formed where an electronic agent performs an action required by law for agreement formation. The same statute provides further in section 20 (b) that a valid and enforceable agreement will be formed where all the parties to a transaction or either one of them uses an electronic agent. The overall effect of these provisions is that an agreement cannot be denied legal validity and enforceability on the ground that an electronic agent was used, whether by one or both parties, to conclude it. Likewise, an agreement cannot be denied legal validity and enforceability on the ground that no human being took part in its formation. Although the ECT Act provides as a general matter that automated transactions are valid and enforceable in South Africa, that statute does not, however, create new rules for the formation of such agreements. This is made clear in section 3, which provides, amongst others, that the ECT Act should not be interpreted to exclude the application of the common law of contract to electronic transactions. Therefore, as with traditional or non-automated agreements, automated transactions too must satisfy the individual requirements of a valid contract at common law. As a matter of fact, the common law theory of contract formation is predominantly based on the assumption that human volition will always play a pivotal role in the making, acceptance or rejection of offers. For that reason, this research proceeds on a strong hypothesis that common law rules and principles pertaining to the formation of agreements are either insufficient or inadequate to accommodate the validity of agreements concluded by computers without the immediate intervention of their users. Consequently, the aim of this research is to discuss how the rules and principles of the common law of contract can be modified or developed in order to accommodate, within the common law theory of contract formation, the statutory validity of automated transactions in South Africa. The discussion of this research is limited to five legal issues, namely the basis of contractual liability in automated transactions, the analysis of offer and acceptance in automated transactions, the time and place of contract formation in automated transactions, the incorporation of standard terms and conditions in automated transactions, and the treatment of mistakes and errors in automated transactions. These issues are discussed first with reference to South African law, primarily with the purpose of determining the extent to which relevant common law rules and principles provide adequate solutions to specific challenges posed by automated transactions. To the extent that relevant common law rules and principles do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this research for their development or modification. As shall be demonstrated in the course of this work, in relation to some of the abovementioned legal issues, the development or modification of common law rules has been done by the ECT Act. These "statutory developments or modifications of the common law" are also discussed in this work, primarily with the aim of determining the extent to which they provide adequate solutions to specific challenges posed by automated transactions. To the extent that these statutory modifications of the common law do not provide adequate solutions to the challenges of automated transactions, recommendations are made in this work on how the relevant provisions of the ECT Act may be interpreted by courts of law or amended by Parliament in order to strengthen the response of that statute. The abovementioned legal issues are also discussed in this work with reference to US and UK law, primarily with the purpose of determining how the law addresses the challenges of automated transactions in these jurisdictions, and to draw valuable lessons for the development or modification of South African contract law.
Keywords: Automated transactions; Autonomous electronic agents; Contract formation; Contract law; Passive electronic agents

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
URI: https://repository.up.ac.za/handle/2263/70768
Keywords: Defective product; Product liability; South Africa; Supply chain

Ex Aequo et Bono as a Response to the ‘Over-Judicialisation’ of International Commercial Arbitration - Teramura, Nobumichi (UNSW Sydney, 2018)
Ex aequo et bono is a long-lived legal concept that enables arbitrators to decide a dispute based on notions of fairness instead of a strict application of legal norms. Jurists generally agree that arbitrators authorised to decide commercial disputes ex aequo et bono can more easily tailor arbitral procedure to achieve an efficient and fair dispute resolution process. They therefore agree that ex aequo et bono arbitration maximises procedural flexibility. However, this flexibility is now perceived more as a negative rather than a positive, despite the potential of ex aequo et bono to mitigate growing concerns about the ‘over-judicialisation’ of arbitration – the increasing formalisation and inefficiency of arbitral procedure. Commentators usually assert that ex aequo et bono introduces excessive unpredictability into arbitration and encourages arbitrators to abuse their discretion. As a result, ex aequo et bono has remained unpopular to this day. This thesis challenges this overly negative conception of ex aequo et bono. It does so particularly under the UNCITRAL Model Law, as an important foundation stone of the global commercial arbitration regime. The thesis investigates significant divergence in the understanding of ex aequo et bono across state jurisdictions and international arbitration institutions. It also analyses the core trends in actual legal practice and in thinking about the principle. The thesis thereby demonstrates that the Model Law requires arbitrators to ensure that their arbitral awards are based on three objective elements: contract terms, trade usages, and mandatory rules of law. Accordingly, while the Model Law allows arbitrators deciding ex aequo et bono to invoke their subjective conceptions of fairness as the ultimate gap-filler when discerning the intention of the parties, the scope for doing so is not unduly expansive. Further, the refinement of various legal theories underpinning international commercial arbitration has enabled parties to determine and challenge more readily the arbitrators’ subjective ideas of fairness. The thesis therefore concludes that the flexibility inherent in ex aequo et bono needs to be both re-evaluated and rejuvenated. It urges the international arbitration community to adopt a revitalised conception of ex aequo et bono to counter-balance the encroaching ‘over-judicialisation’ of arbitration.
Keywords: AI; Amiable composition; Arbitrage; Arbitragem; Arbitration; Arbitration theory; Artificial Intelligence; Blockchain; Cryptocurrency; Ex aequo et bono; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; Trade usages; UNCITRAL Model Law

Aspects of the taxation of company distributions in South Africa - Tredoux, Liezel Gaynor (University of Johannesburg, 2018)
As a company distribution is a means by which wealth is transferred, it is a fertile ground for tax law reform to broaden the tax base and protect South Africa against base erosion and profit shifting. The South African government has identified the corporate tax structure, and many specific corporate tax rules, as areas in South African law in need of reform, and through which the policy objectives of stimulating foreign direct investment, promoting economic growth, and creating more employment opportunities can be achieved. This study involves an analysis on two levels: the corporate tax structure; and the specific tax legislation governing company distributions in South Africa. These aspects are contrasted with comparable rules in Australia and Canada. The study also evaluates the extent to which these laws conform to the normative values of equity, efficiency, certainty, and transparency, with the aim of suggesting improvements to promote South Africa’s current policy objectives. There are a variety of design models for a corporate tax structure. In the context of distributions, the ideal design should resolve whether tax should be paid on profit earned by a company, and also be levied on a second level, on distributions made to the company’s shareholders. Certain jurisdictions merge these two levels of tax to create a single taxable event which avoids the economic double taxation of income. There is, however, no dominant or universal model and several solutions can be mooted. Australia follows an imputation system which taxes corporate income at the first level of tax but grants a tax credit to shareholders on distribution, which means this income is taxed only once. Canada applies a hybrid integration system which also combines the two levels of tax and grants a tax credit to certain individual shareholders on distribution. However, the principles applied in these two models differ. The South African corporate tax structure is a hybrid, dual-rate system in terms of which different rates apply to corporate income and distributions to shareholders. All three systems offer relief for taxpayers which partially eliminates double taxation, with Australia having eliminated it fully for resident shareholders. In broad terms, a company distribution can be made by a company to its shareholders through either a return on capital or a return of capital. The policy approach adopted by the South African government is that all net accretions of wealth by the taxpayer should be taxable. Despite government’s intentions, there is a significant difference in the taxation rules applied to returns of an income nature (dividends and income), on the one hand, and returns of a capital nature (returns of capital, distribution of assets in specie) on the other. In addition, the net accretion of wealth is not always taxable on distribution to shareholders. In most instances the tax liability in respect of the return of capital is either deferred, or alternative rules are created which deviate from the principles and immediate tax liability that apply to returns on capital (dividends and income). In certain instances this deviation is justified, but in others it could lead to inequity between taxpayers and a narrowing of the tax base – both undesirable effects. A number of proposals are made to improve the law applicable to the taxation of company distributions as regards specific transactions. These are aimed, principally, at protecting the South African tax base against base erosion and profit shifting, and aligning South Africa’s tax law with international trends. The study finds that through the application of its hybrid dual-rate corporate tax system, South Africa has reduced economic double taxation to some extent, and that it is unnecessary for South Africa to integrate company- and shareholder-level tax. In addition, a variety of changes are suggested to improve the tax legislation applicable to specific company distributions, and to promote equity, certainty, and revenue collection. The South African tax legislation regulating company distributions is, in the main, fit for purpose, although there is room for improvement when it comes to simplicity, structure, and certainty.
Keywords: Company distributions; Contributed tax capital; Corporate tax; Dividend reinvestment plans; Dividends tax; Economic double taxation; Taxation

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
https://escholarship.mcgill.ca/concern/theses/s1784p10r
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims